RISK FACTORS AND STRUCTURE OF MORTIDITY IN PREMATURE NEWBORNS WITH FATAL OUTCOME - Чистякова, Гузель Нуховна; Ремизова, Ирина Ивановна; Кадочникова, Полина Андреевна; Абакарова, Диана Арсеновна; Гришкина, Анастасия Александровна (Mother and Baby in Kuzbass, 2024)
Despite the introduction of modern nursing technologies, a high number of deaths of premature newborns remains today.Objective – to assess the risk factors and structure of morbidity in premature infants with fatal outcome.Materials and methods. A retrospective analysis of medical documentation and protocols of pathological and anatomical autopsies of newborns was carried out. The 1st group included newborns who died in the early neonatal period (from 1 to 7 days), the 2nd group included children who died in the late neonatal period (from 8 to 28 days).Results. Newborns of groups 1 and 2 were comparable in terms of gestational age, anthropometric parameters, and Apgar score. In the 1st group of children, boys were more often born. According to X-ray data on days 1 and 5, the main diagnoses in premature infants were respiratory distress syndrome (RDS), pneumopathy and pulmonary edema. By the 5th day of life, the development of pneumonia was recorded 4 and 5 times more often in both groups compared to the first day. There were no statistically significant differences in radiographs between groups. In a general blood test in children of the 1st group, a decrease in the percentage of neutrophils and monocytes and an increase in lymphocytes were recorded, relative to the indicators of the 2nd group. The clinical diagnosis of deceased newborns of both groups was dominated by hypoxic-ischemic damage to the central nervous system, multiple organ failure syndrome, and RDS. According to the pathoanatomical autopsy, the causes of death in newborns in the early neonatal period were: male gender, respiratory distress syndrome, canalicular stage of lung development, and in the late period – generalized intrauterine infection.Conclusion. Thus, understanding the structure of the causes of mortality in premature infants helps to improve the quality of medical care in a specialized hospital to increase neonatal survival by focusing on preventive measures.
Keywords: premature newborn; risk factors; death; pathological examination